(untitled) (Advancements in Homeopathic Research, 2023)
Lichen simplex chronicus (LSC) or neurodermatitis is a chronic type of skin disease which features itself as chronic localized and lichenified form of atopic dermatitis. Conventional treatment only keeps the symptoms in abeyance and eruptions reappear again and again. Here a case of LSC, of 60 year old male with a history of one and half year old dry, papular lesions presented. On the basis of the totality of symptoms, Homoeopathic medicine Sepia succus 200C was prescribed and gradually the patient showed stable improvement in signs and symptoms and reached remission by the end of 4 months. There was no recurrence over the next 8 months. Causal attribution of changes in his condition to the Homoeopathic treatment was depicted by modified Naranjo criteria (MONARCH). This case report evidently suggests that Homoeopathy can serve as a possible treatment option for the management of neurodermatitis cases.